Предмет:
Другие предметыАвтор:
анонимПодставляем вместо а и с в выражение данные нам значения:
3а/4с - 9а^2 + 16с^2/12ас + 4с - 9а/3а = (3 * 16)/(4 * 72) - 9 * 16^2 + (16 * 72^2)/(12 * 16 * 72) + 4 * 72 - (9 * 16)/(3 * 16) = 48/288 - 2304 + 82944/13824 + 288 - 3 = 1/6 - 2304 + 6 + 288 - 3 = -2013 + 1/6 = -2012 5/6.
Автор:
nixonДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть